Fiscal Decentralization Dilemma in Indonesia: Between Corruption Accountability and Probability at Local Levels - Fatoni, Agus (Jurnal Bina Praja, 2020)
Decentralization in Indonesia is an unfinished reform and to date, its implementation has not been maximized especially fiscal decentralization. This study aims to investigate the dilemma of fiscal decentralization in Indonesia, between accountability and the probability of corruption at the local level. Data collection in this research is in the form of documentation study to collect secondary data. Secondary data, this study will rely on documentary analysis of official documents from government, NGOs and news items from the media. For data analysis, the study will run analysis processes such as coding, combining emerging codes into themes, verifying themes through theory and follow-up interviews, and drawing conclusions. Whereas the validity mechanism applies member checks, triangulation, multiple sources of data, and looking for counterexamples. This research empirically found that the implementation of fiscal decentralization in Indonesia not only had a positive impact on the financial accountability of local governments but also had a positive impact on the occurrence of corruption in local governments. This means, fiscal decentralization is like two sides of a coin, on the one hand, it is able to increase the financial accountability of local governments, but on the other hand the greater the balance of funds provided by the central government to the regions, the higher the probability of corruption in local governments. Therefore, the supervision of the implementation of fiscal decentralization in order to create good financial governance and minimize corruption in the local government body in Indonesia.